Production Of Bioinput From Arbuscular Mycorrhiza For Agricultural Sustainability (Journal of Namibian Studies : History Politics Culture, 2022)
The objective of this research was to design a process for the production of bio-input from arbuscular mycorrhizal fungi for use in sustainable agricultural production. Practical investigations were developed for the isolation of spores from the soil, determination of the colonizing structures inside the root tissues and the field technique for the production of inoculant for use as a source of biofertilizers. The results show that soil and climatic conditions, plant type and time of year determine spore abundance and colonization effectiveness. A host plant plays a fundamental role for the fungus-plant interaction and the conditions and stages of the colonization process are important for the production of arbuscular mycorrhizal inoculants and their effectiveness in the field. Arbuscular mycorrhizal fungi are a native source of microorganisms as a source for bio-input production and environmentally sustainable agroforestry production.